Comment on "Giant pyroelectric energy harvesting and a negative electrocaloric effect in multilayered nanostructures" by G. Vats, A. Kumar, N. Ortega, C. R. Bowen and R. S. Katiyar, Energy Environ. Sci., 2016, 9, 1335. Issue 3 (16th February 2021) - Chen, Xin; Shvartsman, Vladimir; Lupascu, Doru C.; Zhang, Q. M.
Abstract : In the ferroelectric phase, the change of polarization with temperature from partially switched polarization hysteresis loops has no relation with the electrocaloric effect (ECE) and hence cannot be used in Maxwell relation to deducing ECE. Abstract : Vats et al. (2016) reported a giant negative electrocaloric effect in multi-ferroic layers. The results were deduced using the polarization from partially switched polarization loops and the Maxwell relation on the electrocaloric effect. First of all, fundamentally, the change of these polarizations with temperature, as presented in their Fig. 5, has no relation with the electrocaloric effect and hence cannot be used to deduce the ECE using the Maxwell relation. Moreover, we are troubled by the data presented in their Fig. 6, which were, as claimed by authors, deduced from the polarization data in their Fig. 5 and the Maxwell relation. We find that the ECE results presented in their Fig. 6 have no direct relation with the polarization–temperature data in their Fig. 5.